Methylenetetrahydrofolate Reductase C677T: Hypoplastic Left Heart and Thrombosis. (October 2015) - Spronk, Kimberly J.; Olivero, Anthony D.; Haw, Marcus P.; Vettukattil, Joseph J.
The incidence of congenital heart defects is higher in infants with mutation of methylenetetrahydrofolate reductase ( MTHFR ) gene. The MTHFR C677T gene decreases the bioavailability of folate and increases plasma homocysteine, a risk factor for thrombosis. There have been no reported cases in the literature on the clinical implications of this procoagulable state in the setting of cyanotic heart disease, which itself has prothrombotic predisposition. Two patients with hypoplastic left heart syndrome developed postoperative thrombotic complications, both were homozygous for MTHFR C677T . We present these cases and highlight the implications of MTHFR mutation in the management of complex congenital heart disease.